2022
DOI: 10.3390/jcm11040964
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Differences between Community-Acquired Mycoplasma pneumoniae Pneumonia and COVID-19 Pneumonia

Abstract: Mycoplasmapneumoniae is one of the major causative pathogens of community-acquired pneumonia (CAP). M. pneumoniae CAP is clinically and radiologically distinct from bacterial CAPs. One feature of the Japanese Respiratory Society (JRS) guidelines is a trial to be carried out to differentiate between M. pneumoniae pneumonia and bacterial pneumonia for the selection of antibiotics. The purpose of the present study was to clarify the clinical and radiological differences of the M. pneumoniae CAP and coronavirus di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
1
1
0
4
Order By: Relevance
“…Analysis of the laboratory findings in our study showed that there were significant differences between the two groups in mean leucocyte count, N%, L%, ALT levels, AST levels, LDH levels and incidence of accelerated PCT. Similar to a previous study, the perpheral leucocyte count of the patients with MPP is usually normal at less than 10,000/UL ( 17 ). The higher leucocyte counts and PCT levels may suggest that the inflammation of Streptococcus pneumoniae pneumonia is more serious than that of Mycoplasma pneumoniae pneumonia.…”
Section: Discussionsupporting
confidence: 84%
“…Analysis of the laboratory findings in our study showed that there were significant differences between the two groups in mean leucocyte count, N%, L%, ALT levels, AST levels, LDH levels and incidence of accelerated PCT. Similar to a previous study, the perpheral leucocyte count of the patients with MPP is usually normal at less than 10,000/UL ( 17 ). The higher leucocyte counts and PCT levels may suggest that the inflammation of Streptococcus pneumoniae pneumonia is more serious than that of Mycoplasma pneumoniae pneumonia.…”
Section: Discussionsupporting
confidence: 84%
“…Эти симптомы выявлялись и по данным других исследований [6,7]. Помимо этого, для бактериальной пневмонии были характерны наличие мокроты и боли в грудной клетке [6][7][8][9]. Односторонний характер инфильтрации, как признак ВБП, также описан другими исследователями [6,10,11].…”
Section: рис номограмма вероятности наличия у пациента с внебольнично...unclassified
“…В нашем исследовании у пациентов с ВБП чаще на блюдались одышка, наличие мокроты, боль в грудной клетке, насморк, озноб и снижение уровня сознания, для вирусного поражения легких была более харак терна общая слабость, при этом озноб и общая сла бость оказались наиболее значимыми симптомами и в многофакторном регрессионном анализе. Похожие дан ные есть и в литературе: выделение мокроты [5][6][7][8], на рушение сознания [7], боль в грудной клетке [7,8] чаще описывают при бактериальной пневмонии, а общую сла бость [5] -при COVID19.…”
Section: Introductionunclassified
“…Среди возбудителей бактериальной пневмонии наиболее вы сокая доля была характерна для Streptococcus pneumoniae, в группе вирусного поражения легких преобладал SARSCoV2. В многофакторном анализе наличие озноба (ОШ и 95% ДИ: 22,1 [6,6], р < 0,001), односторонней инфильтрации по данным рентгенографии или КТ ОГК (ОШ и 95% ДИ: 17,9 [7,1], р < 0,001), снижение уровня сознания (ОШ и 95% ДИ: 3,2 [1,[2][3][4][5][6][7][8]5], р = 0,019), назначение вазопрессоров в первые 24 ч. госпитализации (ОШ и 95% ДИ: 11,8 [2,9], р = 0,002), более высокие значения ЧСС (ОШ и 95% ДИ: 9,1 [2,6], р = 0,003) и ин декса нейтрофилы/лимфоциты (ОШ и 95% ДИ: 1,4 [1,1-1,9], р = 0,021), а также отсутствие об щей слабости (ОШ и 95% ДИ: 0,2 [0,08-0,4], р < 0,001) и более низкие значения общего белка (ОШ и 95% ДИ: 0,2 [0,02-1,00], р = 0,049) более характерны для бактериальной пневмонии по сравнению с вирусным поражением легких. Выводы.…”
unclassified